Mark Harris as a Naturalistic Theist: The Perspective of the Model of Levels of Analysis - Bylica , Piotr (Filozoficzne Aspekty Genezy, 2021)
Presently, naturalistic theism is the dominant position in the debate on the relation between science and religion, defending a thesis that the conflict between science and religion is only an apparent one. Also, this version of theism accepts the naturalist assumptions behind contemporary science and attempts to reformulate the beliefs held within the traditional Christian theism in order to present the religious view of reality as not conflicting with the scientific picture of the world. Certain assumptions behind Mark Harris’s views on the relations between science and religion can be described as consistent with naturalistic theism. The model of levels of analysis helps to analyze the most important themes found within naturalistic theism and show how these are described in the works of Harris. The model facilitates the identification of the relations between particular kinds of assumptions behind the position taken from the point of view of naturalistic theism in the debate on the relation between science and religion. The list of most frequently recurring assumptions — that are also important in Harris’s writings — include: the general division of epistemic competence, which assumes theology (religion) to be competent in dealing with the metaphysical issues (Levels 1 and 2) and science to be the only one competent to deliver the empirical statements describing processes and entities found within the empirical sphere (Levels 4 and 5); the acceptance of the naturalistic assumptions behind contemporary science (Level 2) and skepticism toward the religious notions found in the traditional Christian theism describing supernatural interventions and toward the dualist interpretation of human soul (Level 3). This leads to the acceptance of purely scientific, naturalistic, explanations of the events found within the empirical sphere and to skepticism toward the literal meaning of descriptions of empirical events (Level 5) that are not consistent with the anti-interventionist assumptions behind science. Harris’s acceptance of naturalistic theism in terms of the relation between science and religion and his use of the techniques found in the modern biblical scholarship have led him to the ideas of plurality of meanings and the lack of one definite truth with respect to the specific issues he deals with. From the point of view of MLA it is the rejection of super-naturalistic assumptions of the traditional Christian theism and the acceptance of the naturalistic assumptions of science that seems to be the cause of lack of definite truth in his theological explanations.